Propuesta de intervención arquitectónica de la villa patrimonial “María Trinidad” Barrio Bellavista, Riobamba, Ecuador - Cepeda Naranjo, Melanie Piedad (2023)
The Bellavista citadel has been a place full of story and patrimony across the time. However, housing in the sector is very affected because of ignorance, abandonment and the high economic value that requires maintenance of these houses for their owners. Because of this, this project is centered on one house intervention; “Maria Trinidad” is the patrimonial house, which, through a design proposal, keeps in mind the actual state and deterioration of the building. The proposal is developed in several stages, starting with the knowledge of specific terms that have to do with patrimonial buildings, analyzing regulations, national, international, and local decrees, benchmark analysis, the actual state of the building diagnosis, which has an architectural, pathological and constructive survey in which guidelines and strategy are being applied thanks to the previous investigation. The result is the proposal of a new use for the house that contributes to the urban environment by enhancing it and giving it a new value to the citadel of Bellavista